Pengembangan Absensi berbasis Mobile Aplikasi pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Bone - Syahrul Usman; Jeffry Jeffry; Firman Aziz (Jurnal Teknologi Terpadu, 2021)
Since being designated a global pandemic by the world health agency (WHO), the Corona Virus Disease (Covid-19) outbreak has become a scourge worldwide; various standard transmission control procedures have been set by WHO to break the chain of transmission.  Bone District Government through the Circular of the Regional Secretary No. 800/1919/VI/BKPSDM/2020 dated June 4, 2020, regarding the work system of State Civil Apparatus Employees (ASN) in the new standard order regulates employee attendance using manual attendance and not using fingerprint attendance machines, and this will undoubtedly affect the recording of the performance of each ASN where the attendance data is already connected to the e-performance application that is applied to the Bone district. The purpose of this research is to create an online attendance application based on Android Mobile to be an alternative way of being absent by using the data communication method using the Representational State Transfer (Rest) web service architecture and utilizing the HTTP protocol with JavaScript Object Notation (JSON) format and the Java programming language as a language. Mobile Application programming. The results of this study are a mobile-based attendance application that has been tested for web service performance using the Apache JMeter application to ensure this application is ready to be used simultaneously by many ASN.